The atlantis gene [dramatized adaptation] eaudiobook The origin mystery 1. - Riddle, A.G (Origin Mysteries, 2024)
"Experience the first dramatized audiobook in A.G. Riddle's groundbreaking Origin Mystery Trilogy—the series that has been translated in 24 languages and sold over THREE MILLION COPIES worldwide. In Antarctica, a research expedition discovers an ancient structure buried deep in the ice. In Indonesia, a genetics researcher identifies a breakthrough treatment for autism. But these two incredible discoveries aren't what they seem. They will set off a race to unravel the deepest secrets of human existence—the true history of human origins. And an event that could change humanity forever. Adapted from the novel and produced with a full cast of actors, immersive sound effects and cinematic music! Performed by Richard Rohan, Danny Gavigan, Jonathan David Bullock, Stephanie Németh-Parker, Joel David Santner, Jonathan Sleep, Jenna Sharpe, Andy Clemence , Andrew James Spooner, David Cui Cui, Jacob Yeh, Wayne LeGette, Ryan Carlo Dalusung, Robb Moreira, John Kielty, Kiran Kumar, Tony Nam, Ian Russell, RJ Bayley, James J Johnson, Matthew Pauli, Earl Fisher, Danny Montooth, Crystal Lee, Bruce Alan Rauscher, Yasmin Tuazon, Joe Mallon and Bradley Foster Smith."